THE EFFECT OF PAIR TRAINING VARIATION ON THE SEPAK SILA SKILL OF TAKRAW ATHLETES - Agussalim Agussalim; Suaib Nur; Puspa Sari (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2023)
The skill of Sepak sila is one of the basic techniques in the game of takraw. The focus of this research is extracurricular students at SMA Negeri 1 Palopo. The problem is the lack of variation in pair training. The purpose of this study is to determine whether or not there is an impact of variations in pair training on the sepak sila skills of the takraw extracurricular students at SMA Negeri 1 Palopo. The term